Development of A Floating Market-Based BioPhy Magazine to Train the Religious Characters of Pre-Service Science Teachers - Fitriah, Lutfiyanti; Ita, Ita (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2022)
This study aimed to describe the validity of the integration of religious values in BioPhy magazine and the religious character of pre-service science teachers when using the Floating Market-based BioPhy magazine. These religious values are related to the concept of fluidity, biodiversity, ecosystem, and the local character of South Kalimantan society, namely kayuh baimbai. This research was development research with Tessmer formative evaluation model. The test subjects to determine the religious character of students were 10 students from the Chemistry Education Department in the small group trial and 43 students from Biology Education Department in the field test. Both subjects were currently attending Fluid lectures in the 2021/2022 academic year in the Basic Physics course. Data were obtained through validation sheets, a self-evaluation inventory of religious characters, and observation sheets. Data were analyzed quantitatively and qualitatively. The results showed that integrating religious values in magazines was valid, with the Aiken validity coefficient ranging from 0.92 to 1.00. In addition, pre-service chemistry teachers have a religious character with an average score of 4.71, and pre-service biology teachers have a religious character with an average score of 4.77 in the affective domains A1 to A5 based on Bloom's taxonomy. The religious character of the two test subjects was categorized as very good. Thus, the Floating Market-based BioPhy magazine can be used to train the religious character of Pre-Service Science teachers. The developed magazine can be used in the Basic Physics course. Future research could be piloted for a larger sample as this research was limited to a not-so-large sample, and the magazine was developed only on fluid topics in the Basic Physics course.